Cardiac Manifestations of Myotonic Dystrophy in a Pediatric Cohort - Laia Brunet Garcia; Laia Brunet Garcia; Ankita Hajra; Ella Field; Joseph Wacher; Helen Walsh; Gabrielle Norrish; Adnan Manzur; Francesco Muntoni; Pinki Munot; Stephanie Robb; Rosaline Quinlivan; et al. (Frontiers in Pediatrics, 2022)
Myotonic dystrophy type 1 (DM1) is the most prevalent inherited neuromuscular dystrophy in adults. It is a multisystem disease with cardiac manifestations. Whilst these are well-defined in adults, there are scarce published data in the pediatric population. This study aimed to investigate the yield and progression of cardiac disease in pediatric DM1 patients, focusing on congenital DM1 (cDM1).MethodsA retrospective observational study of all pediatric DM1 patients referred to our center (December 2000-November 2020) was conducted. Patients were classified into DM1 forms according to age of symptom onset and disease severity. Patients underwent clinical and cardiac evaluation with 12-lead ECG, transthoracic echocardiography and 24-h ECG Holter monitoring.Results67 DM1 pediatric patients were included: 56 (83.6%) cDM1 and 11 (16.4%) non-cDM1. Median follow-up time of cDM1 patients was 8.0 [3.25–11.0] years. 49 (87.5%) cDM1 patients had baseline 12-lead ECG and 44 (78.6%) had a follow-up 12-lead-ECG, with a median follow-up time from diagnosis to baseline ECG of 2.8 [1.0–8.5] years and to follow-up ECG of 10.9 [5.7–14.2] years. Overall, 43 (87.8%) presented ECG abnormalities, most commonly in the form of asymptomatic conduction disease (n = 23, 46.9%), of which 21 (42.9%) had first degree atrioventricular block (1st AVB). There was an increase of prevalence from baseline to follow-up ECG in low QRS voltage (16.7%), poor R wave progression (13.9%), abnormal repolarisation (11.9%) and 1st AVB (7.6%). one patient (1.8%) underwent pacemaker implantation for syncope in the context of progressive conduction disease. No patients developed left ventricular systolic dysfunction. 4 (7.1%) cDM1 patients died during follow up, including three who died suddenly with no clear cause of death.ConclusionsThis study is the first to analyse the prevalence and progression of ECG abnormalities in cDM1 pediatric patients. The high prevalence of abnormal findings, progressive changes and number of potentially associated events (1 pacemaker implantation and 3 unexplained sudden deaths) stresses the importance of systematic and continued cardiac evaluation of these patients.